BTC as a Novel Biomarker Contributing to EMT via the PI3K-AKT Pathway in OSCC - Shen, Ting; Yang, Tianru; Yao, Mianfeng; Zheng, Ziran; He, Mi; Shao, Mengying; Li, Jiang; Fang, Changyun (Frontiers in Genetics, 2022)
Purpose: Oral squamous cell carcinoma (OSCC) is one of the most common malignant tumors of the head and neck, while metastasis is the main cause of OSCC-related death. There is an urgent need to explore novel prognostic biomarkers and identify biological targets related to metastasis in OSCC treatment. Methods: Analysis of differential expression were performed using datasets in the Cancer Genome Atlas (TCGA) and Gene Expression Omnibus (GEO). Immunohistochemistry (IHC) were conducted to assess the expression of betacellulin (BTC) in OSCC. SCC4 and CAL27 cells were use for in vitro experiments, in which CCK-8, transwell assays, wounding healing assays were performed to verify the biological functions of BTC. The role of BTC in EMT were analyzed by EMT score and western blot. Results: Through the analysis of the mRNA expression profile data from the TCGA database in OSCC, we found only low expression of BTC was significantly correlated with a poor prognosis in OSCC patients. The results of IHC assays and TCGA databases showed the expression level of BTC were related to tumor stage, histological grade, and metastasis status. In vitro analysis showed that overexpression of BTC significantly suppressed the proliferation and migration of OSCC cells. Furthermore, we confirmed that BTC could affect EMT through the PI3K-AKT signaling pathway. Conclusions: BTC deficiency induces the proliferation, migration and EMT of OSCC cells via the PI3K-AKT pathways, leading to a poor prognosis in OSCC. BTC may be used as a novel molecular marker to assess the prognosis of OSCC patients.